Acceptance analysis students using technology acceptance model on students of biology education program of Syiah Kuala University and Ar-raniry State Islamic University - Millati Ahya; Ismul Huda; Supriatno Supriatno (Jurnal Edubio Tropika, 2018)
This research uses TAM (technology acceptance model)model with six constructs that are used are computer self-efficacy (CSE), perceived ease of use (PEOU), perceived usefulness (PU), attitude toward technology use (attitude Towards using technology / AT), intention to use (IU), and Frequency of Use (FU). This model is then used to examine which is an e-learning technology used in Biology Education Department of Syiah Kuala University and UIN Ar-Raniry. This study aims to determine the relationship between the factors that affect the acceptance and use of ebelajar.web.id at Syiah Kuala University and UIN Ar-Raniry. The type of research used in this research is explanatory research with data analysis technique using Part Least Square (PLS) approach. The method used to collect data is survey method. Data obtained from respondents who are students of Biology Education Faculty of Teacher Training and Education Universitas Syiah Kuala and Biology Education Faculty of Tarbiyah and Teacher Training of Ar-Raniry State Islamic University in the second semester of academic year 2016/2017 taking Information Technology and Computer and Ecology Course and environmental issues. The sample was 99 samples. The results of the data analysis were obtained as follows: (1) The CSE construct has significant effect on the PU construct; (2) CSE construct has significant effect on PEU construct; (3) PEU construction has significant effect on PU construct; (4) PEU construction has significant effect on construct A PU; (5) PEU construction has significant effect on IU construct; (6) PU construction has significant effect to construct A; (7) construct A has significant effect on IU construct. The conclusion in this research is that there are factors influencing to the acceptance level of learning technology using TAM model.